Equine glucagon-like peptide-1 receptor physiology - Murad H. Kheder; Simon R. Bailey; Kevin J. Dudley; Martin N. Sillence; Melody A. de Laat (PeerJ, 2018)
Background Equine metabolic syndrome (EMS) is associated with insulin dysregulation, which often manifests as post-prandial hyperinsulinemia. Circulating concentrations of the incretin hormone, glucagon-like peptide-1 (GLP-1) correlate with an increased insulin response to carbohydrate intake in animals with EMS. However, little is known about the equine GLP-1 receptor (eGLP-1R), or whether GLP-1 concentrations can be manipulated. The objectives were to determine (1) the tissue localisation of the eGLP-1R, (2) the GLP-1 secretory capacity of equine intestine in response to glucose and (3) whether GLP-1 stimulated insulin secretion from isolated pancreatic islets can be attenuated. Methods Archived and abattoir-sourced tissues from healthy horses were used. Reverse transcriptase PCR was used to determine the tissue distribution of the eGLP-1R gene, with immunohistochemical confirmation of its pancreatic location. The GLP-1 secretion from intestinal explants in response to 4 and 12 mM glucose was quantified in vitro. Pancreatic islets were freshly isolated to assess the insulin secretory response to GLP-1 agonism and antagonism in vitro, using concentration-response experiments. Results The eGLP-1R gene is widely distributed in horses (pancreas, heart, liver, kidney, duodenum, digital lamellae, tongue and gluteal skeletal muscle). Within the pancreas the eGLP-1R was immunolocalised to the pancreatic islets. Insulin secretion from pancreatic islets was concentration-dependent with human GLP-1, but not the synthetic analogue exendin-4. The GLP-1R antagonist exendin 9-39 (1 nM) reduced (P = 0.08) insulin secretion by 27%. Discussion The distribution of the eGLP-1R across a range of tissues indicates that it may have functions beyond insulin release. The ability to reduce insulin secretion, and therefore hyperinsulinemia, through eGLP-1R antagonism is a promising and novel approach to managing equine insulin dysregulation.